Analisis Pembiayaan Bermasalah Pada BMT Mitra Khazanah Palembang - Warikon Wasi; Deky Anwar; M. Iqbal (CV. Cendikiawan Muda Sriwijaya, 2024)
This study aims to analyze the factors that cause problematic financing and analyze the strategies used in dealing with problematic financing at BMT Mitra Khazanah Palembang. The analytical method used in this study is a qualitative method with data collection techniques in the form of interviews, discussions with the parties who manage BMT Mitra Khazanah Palembang, as well as from several other article sources. From the research that has been carried out, it is found that there are two factors that cause problematic financing at BMT Mitra Khazanah Palembang, namely internal and external factors. In internal factors there are several causes, including Weaknesses in Analyzing and Lack of Employees or Human Resources (HR). Meanwhile, in external factors, there are also several causes, including the Covid-19 Pandemic and Bankruptcy or Customer Business Failure. In addition, BMT Mitra Khazanah Palembang implements several ways to overcome non-performing financing, including Rescheduling, Reconditioning, Restructuring, Collateral Foreclosure